RePLEX: A Model-Based Reengineering Tool for PLEX Telecommunication Systems - Fuss, Christian; Mosler, Christof; Pettau, Marcel (Electronic Communications of the EASST, 2007)
Maintenance of complex legacy software systems is a challenging task. In the first place, maintenance requires understanding the system. Reverse engineering and reengineering tools, which make the design of the current system available on-line and which support planning and performing changes to the system, are urgently needed. We present a new tool for reengineering telecommunication systems, recovering the current architecture, and extracting state machines reflecting the system behavior. The tool is based on a structure graph of the architecture and allows architectural modifications with according code changes. The modifications are specified as graph transformations using FUJABA enabling the generation of a Java prototype, which is accessible via a GUI based on the Graphical Editor Framework (GEF) plug-in for the Eclipse workbench.